A Guide for Soil Health and Fertility for Maize production in Kenya - Nyaga, Patrick; Yegon, Rebecca; Laub, Moritz; Six, Johan (UoEm, 2023)
The health of your soil is a fundamental aspect of successful farming. However, many arable soils in Kenya have degraded and lost fertility over recent decades1. This is expected because many soils were recently transformed from more permanent land uses, which always leads to soil fertility losses2. However, this soil fertility loss is largely avoidable with best management practices that replenish soil organic matter and soil nutrient resources3,4.
Guide